Softskill Development of Al-Islam Teachers in Ismuba Learning in Creative Schools: Pengembangan Softskill Guru Al-Islam Dalam Pembelajaran Ismuba di Sekolah Kreatif - Muhammad Faris; Anita Puji Astutik (Universitas Muhammadiyah Sidoarjo, 2022)
In the era of globalization, the industrial era 4.0 is now starting to appear competition in various fields. The field of education in this era demands quality graduates who are ready to compete. Quality student graduates are obtained from a systematic, efficient, effective, and interesting learning process. Good learning is obtained from a teacher who is competent, qualified, and has soft skills who play a role in learning. The magnitude of the teacher's role in learning shows that the teacher is an important aspect of learning. Based on the function and role, the teacher must have soft skills in improving the quality of learning. The development of teacher skills is an obligation in order to produce teachers who are competent, creative, innovative, and able to communicate in overcoming all educational problems. Especially in the face of developments such as today. This research uses descriptive qualitative research. The sources of data used are primary and secondary data. Primary data were obtained from observations and interviews with teachers at SD Muhammadiyah 2 Tulangan. The data will be analyzed by descriptive analysis method. The theoretical basis used is the interpretation of data according to Mules and Hubermen. Based on the data analysis conducted, it is concluded that the development of soft skills for ISMUBA teachers at SD Muhammadiyah 2 Tulangan can be said to be good because it is in accordance with the indicators and 4 teacher competencies. In the development of soft skills for ISMUBA SD Muhammadiyah 2 Tulangan teachers, there are still things that have not been fulfilled, namely in the aspect of assessment. The inhibiting factor in improving soft skills lies within the individual teacher himself, which can be seen from the lack of empathy and discipline.